Self-healing electrolyte membrane for lithium ion battery and preparation method thereof

CN118040072BActive Publication Date: 2026-10-23SHANGHAI UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410359559.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2026-10-23
Estimated Expiration
2044-03-27

AI Technical Summary

Technical Problem

[0004]同时,具有自修复能力的聚合物电解质膜也应运而生,如公告号CN 113193235B公开了一种自修复聚合物电解质膜,该自修复聚合物电解质膜能够在给定条件下缓释多胺小分子单体,从而以进行化学反应的方式消除锂枝晶,实现聚合物电解质膜的自愈;很明显,随着多胺小分子单体的释放,其自修复能力势必会随之下降

Benefits of technology

[0032]本公开的用于锂离子电池自修复电解质膜,成膜成分中的甲基丙烯酸糠酯单体(F-MA),该单体的马来酰亚胺部分能够与呋喃反应生成高密度共价交联网络,既可作为交联基促进自修复聚合物的强度,又可作为自愈基触发Diels-Alder反应,Diels-Alder反应加合物中二烯和二亲核试剂之间的键合强度远低于其他键,如C-C键、C-O键等;当膜受损之后,对其进行加热时,甲基丙烯酸糠酯单体上的糠基和马来酰亚胺基团会重新键合,从而使膜获得自修复的能力;而且本发明的自修复电解质膜是一种改性膜,不存在小分子释放等过程,自修复能力的持久性不会被破坏,所以通过本发明的自修复电解质膜能延缓电解质的退化过程,最终可以达到延长锂离子电池使用寿命的目的。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118040072B_ABST
    Figure CN118040072B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a self-repairing electrolyte film for lithium ion batteries and a preparation method thereof, the preparation method comprising: preparing a self-repairing polymer precursor by emulsion polymerization of methyl methacrylate, butyl acrylate and furfuryl methacrylate; and coating a mixed solution containing the self-repairing polymer precursor, a lithium salt and a crosslinking agent on a substrate until a dry film is formed to obtain a self-repairing polymer electrolyte film; the self-repairing electrolyte film of the present disclosure is a modified film, has a persistent self-repairing ability, can delay the degradation process of the electrolyte through the self-repairing electrolyte film, and ultimately achieves the purpose of prolonging the service life of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of lithium-ion battery technology, specifically to a self-healing solid polymer electrolyte membrane for manufacturing lithium-ion batteries and its preparation method. Background Technology

[0002] Currently, lithium-ion polymer batteries are quite satisfactory for portable electronic products, favored for their high energy density, fast charge / discharge rates, and long cycle life. However, during battery charging and discharging, lithium ions deposit on the electrode surface. This deposition is often uneven, and excessively high lithium-ion concentrations can lead to the formation of lithium dendrites. The growth of lithium dendrites can cause physical damage to the polymer electrolyte membrane, potentially leading to safety issues such as short circuits and leakage, and even serious accidents such as overheating, fire, or explosion. These failures severely limit the reliability and lifespan of lithium-ion batteries, causing widespread malfunctions in electronic devices, generating large amounts of electronic waste, causing inconvenience, and posing safety hazards.

[0003] To address the aforementioned issues, current research primarily focuses on improving the safety of lithium-ion batteries by constructing electrode materials with high stability and resistance to lithium dendrite formation, such as porous materials and surface coatings, to reduce lithium dendrite formation. Alternatively, appropriate charging control strategies, such as limiting the charging rate or using constant current charging, can be employed to control the temperature and current density during battery charging, thereby reducing the possibility of uneven lithium-ion deposition.

[0004] Meanwhile, self-healing polymer electrolyte membranes have emerged. For example, CN 113193235B discloses a self-healing polymer electrolyte membrane that can slowly release polyamine small molecule monomers under given conditions, thereby eliminating lithium dendrites through a chemical reaction and achieving self-healing of the polymer electrolyte membrane. Obviously, as the polyamine small molecule monomers are released, its self-healing ability will inevitably decrease. Therefore, it is necessary to study self-healing polymer electrolyte membranes whose self-healing ability does not degrade over time or degrades slowly. Summary of the Invention

[0005] In view of this, this disclosure provides a self-healing electrolyte membrane for lithium-ion batteries and a method for preparing the same, solving the problem that the self-healing ability of current self-healing electrolyte membranes for lithium-ion batteries is not durable.

[0006] The technical concept of the self-healing electrolyte membrane and its preparation method in this invention is as follows: Methyl methacrylate (MMA) is modified with furfuryl alcohol (FA) to obtain furfuryl methacrylate monomer (F-MA). The maleimide portion of this monomer can react with furan to form a high-density covalent cross-linked network. This network can act as a cross-linking group to promote the strength of the self-healing polymer and as a self-healing group to trigger the Diels-Alder reaction. The bonding strength between the diene and the dinucleophile in the Diels-Alder adduct is much lower than that of other bonds, such as C-C bonds and CO bonds. When the sample is damaged and heated, the furfuryl group and the maleimide group on the furfuryl methacrylate monomer will re-bond, thereby enabling the material to acquire self-healing capabilities.

[0007] Simultaneously, a tough, flexible, self-healing precursor polymer was prepared by emulsion polymerization of monomers, including methacrylate (MMA), butyl acrylate (BMA), and furfuryl methacrylate (F-MA), in a molar ratio of 1:2:1. Then, by adding N,N'-4,4'-diphenylmethane-bismaleimide (BMI) to an N-methylpyrrolidone (NMP) solution containing the precursor polymer and lithium salt, a mechanically stable polymer matrix that can form crosslinks in situ was obtained, specifically a modified self-healing electrolyte membrane, which supports lithium-ion transport pathways and thermal response self-healing capabilities.

[0008] When the membrane is damaged, causing a short circuit, the battery heats up rapidly due to the large current flowing through it. Therefore, the generated heat can repair the fractured area, restoring the self-healing polymer electrolyte membrane to its function. In principle, this process does not require additional formulation components such as catalysts, additional monomers, or special treatment of the fracture interface to repeatedly repair the fractured parts of the polymer electrolyte. Therefore, the assembled lithium-ion battery is an ideal self-healing lithium-ion battery.

[0009] To solve the above-mentioned technical problems, in a first aspect, the present disclosure provides a method for preparing a self-healing electrolyte membrane for lithium-ion batteries, comprising:

[0010] A self-healing polymer precursor was prepared by emulsion polymerization of methacrylate, butyl acrylate and furfuryl methacrylate.

[0011] The self-healing electrolyte membrane is obtained by coating a mixed solution containing the self-healing polymer precursor, lithium salt and crosslinking agent onto a substrate until a dry film is formed.

[0012] In this disclosure and possible embodiments, the method for preparing the self-healing polymer precursor includes:

[0013] The methacrylate, butyl acrylate and furfuryl methacrylate are added to the emulsifier according to the set ratio, and the mixture is stirred in an inert atmosphere to form an emulsion.

[0014] An initiator is added to the emulsion to carry out the emulsion polymerization. The precipitate of the emulsion polymerization product is purified and dried to obtain the self-healing polymer precursor.

[0015] In this disclosure and possible embodiments, the set ratio is a molar ratio of methacrylate, butyl acrylate and furfuryl methacrylate of 1:2:1;

[0016] The emulsifier is sodium dodecyl sulfate with a mass concentration of 2.5%, prepared under a nitrogen atmosphere, using deionized water as a solvent, and at 60°C.

[0017] The initiator is ammonium sulfate.

[0018] In this disclosure and possible embodiments, the method for preparing the mixed solution comprising the self-healing polymer precursor, lithium salt, and crosslinking agent includes:

[0019] At a set temperature, the self-healing polymer precursor and the lithium salt are mixed in a solvent, and then the crosslinking agent is added to the mixture and completely dissolved to obtain the mixed solution.

[0020] In this disclosure and possible embodiments, the set temperature is 50°C;

[0021] The solvent is N-methylpyrrolidone;

[0022] The lithium salts include lithium diborate and lithium lithium oxalate.

[0023] The crosslinking agent is N,N'-4,4'-diphenylmethane-bismaleimide.

[0024] In this disclosure and possible embodiments, the method for preparing furfuryl methacrylate includes:

[0025] An anhydrous tetrahydrofuran solution of methacryloyl chloride was added dropwise to an anhydrous tetrahydrofuran solution of furfuryl alcohol and triethylamine prepared at 0°C. After the addition was completed, the mixture was stirred at room temperature for a set time to obtain the reaction product.

[0026] After concentrating the filtrate of the reaction product under vacuum conditions, the concentrate is purified by column chromatography to obtain furfuryl methacrylate.

[0027] In this disclosure and possible embodiments, the molar ratio of furfuryl alcohol, triethylamine, and methacrylamide chloride is 1:1:1;

[0028] The stirring reaction time is set to 3 hours;

[0029] The solvent used for column chromatography purification was petroleum ether / ethyl acetate at a mass ratio of 40:1.

[0030] Secondly, the self-healing electrolyte membrane for lithium-ion batteries is specifically prepared using the preparation method described in the first aspect.

[0031] The beneficial effects of this invention are as follows:

[0032] The self-healing electrolyte membrane for lithium-ion batteries disclosed herein comprises a furfuryl methacrylate monomer (F-MA) in its film-forming component. The maleimide portion of this monomer can react with furan to form a high-density covalent cross-linked network. This network can act as a cross-linking group to promote the strength of the self-healing polymer and as a self-healing group to trigger the Diels-Alder reaction. The bonding strength between the diene and the dinucleophile in the Diels-Alder adduct is much lower than that of other bonds, such as C-C bonds and CO bonds. When the membrane is damaged, heating it will cause the furfuryl group and the maleimide group on the furfuryl methacrylate monomer to re-bond, thereby giving the membrane the ability to self-heal. Moreover, the self-healing electrolyte membrane of this invention is a modified membrane, and there is no process such as the release of small molecules. The durability of the self-healing ability is not compromised. Therefore, the self-healing electrolyte membrane of this invention can delay the degradation process of the electrolyte, ultimately achieving the goal of extending the service life of lithium-ion batteries. Attached Figure Description

[0033] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this disclosure and, together with the specification, serve to illustrate the technical solutions of this disclosure.

[0034] Figure 1 This is a flowchart of the preparation method of the self-healing electrolyte membrane for lithium-ion batteries according to the present invention;

[0035] Figure 2 The present invention provides a synthetic and design route for the molecular structures of MA-F, self-healing polymer precursors, and self-healing electrolyte membranes.

[0036] Figure 3 Optical images of the self-healing electrolyte membrane self-healing process in Embodiment 1 of this disclosure;

[0037] Figure 4 Here is a scanning electron microscope image of the self-healing electrolyte membrane of Embodiment 1 of this disclosure;

[0038] Figure 5 The tensile strength of the self-healing electrolyte membrane of Embodiment 1 of this disclosure;

[0039] Figure 6 The discharge capacity of the PE membrane and the self-healing electrolyte membrane in Embodiment 1 of this disclosure under different C-rate cycles is shown. Detailed Implementation

[0040] The present disclosure is described below based on embodiments; however, it is worth noting that the present disclosure is not limited to these embodiments. In the detailed description of the present disclosure below, certain specific details are described in detail. However, those skilled in the art will fully understand the present disclosure for the parts not described in detail.

[0041] Furthermore, those skilled in the art should understand that the accompanying drawings are for illustrative purposes, features, and advantages of this disclosure only, and are not actually drawn to scale. Also, unless the context explicitly requires it, the words "comprising," "including," and similar terms throughout the specification and claims should be interpreted as encompassing rather than exclusive or exhaustive; that is, meaning "including but not limited to."

[0042] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.

[0043] Figure 1 This is a flowchart of the preparation method of the self-healing electrolyte membrane for lithium-ion batteries according to the present invention; Figure 2 This disclosure outlines the synthetic and design route for the molecular structures of MA-F, the self-healing polymer precursor, and the self-healing electrolyte membrane. Figure 1 Combination Figure 2 As shown in the specific embodiment of this disclosure, the method for preparing a self-healing electrolyte membrane for a lithium-ion battery preferably includes the following steps:

[0044] 1. Preparation of the functional monomer furfuryl alcohol methacrylate, the specific preparation process is as follows:

[0045] (1) According to the molar ratio of furfuryl alcohol, triethylamine and methacryloyl chloride of 1:1, the set amount of furfuryl alcohol and triethylamine were dissolved in anhydrous tetrahydrofuran and stirred at 0℃ for 2h to obtain a homogeneous solution, which was recorded as the first solution.

[0046] (2) Weigh out a set amount of methacryloyl chloride and dissolve it in anhydrous tetrahydrofuran, which is recorded as the second solution. Add the second solution dropwise to the first solution. During the dropwise addition, the system temperature is kept at 0℃. After the dropwise addition is completed, continue to stir the reaction at room temperature for 3 hours to obtain the reaction product.

[0047] (3) After filtering out the triethylamine hydrochloride precipitate in the reaction product, the filtrate was concentrated under vacuum. Then the concentrated product was purified by silica gel rapid column chromatography. The elution solvent was petroleum ether / ethyl acetate with a mass ratio of 40:1. After evaporating the solvent, the purified product F-MA was separated and collected as a pale yellow oil.

[0048] 2. A self-healing polymer precursor was prepared by emulsion polymerization. The specific preparation process is as follows:

[0049] (1) Using deionized water as solvent, a sodium dodecyl sulfate solution with a mass concentration of 2.5% was prepared under a nitrogen atmosphere and at 60°C and used as an emulsifier.

[0050] (2) Add methacrylate (MMA), butyl acrylate (BMA), and furfuryl methacrylate (F-MA) to a 2.5 wt% sodium dodecyl sulfate solution in a molar ratio of 1:2:1, and continue stirring under a nitrogen atmosphere for 2 h to form an emulsion.

[0051] (3) Using ammonium sulfate as an initiator, the initiator was added and stirred continuously for 6 hours to obtain an emulsion-like emulsion polymerization product.

[0052] (4) The emulsion polymerization product was introduced into a 3wt% Al2(SO4)3 solution to form a precipitate. The precipitate was filtered and separated, and then washed with hot deionized water (55℃) to remove residual monomers and emulsifiers and other impurities. The water-washed and purified precipitate was then placed in a vacuum oven and dried at 60℃ for 12h to obtain the MMA-BMA-(F-MA) self-healing polymer precursor. The self-healing polymer precursor was placed in a desiccator for subsequent preparation of the electrolyte membrane.

[0053] 3. Preparation of a self-healing electrolyte membrane, the specific preparation process is as follows:

[0054] (1) At 50°C, using N-methylpyrrolidone (NMP) as a solution, the MMA-BMA-(F-MA) self-healing polymer precursor and lithium salt were stirred and mixed for 1 h to obtain a uniform first mixed solution. The preferred lithium salt is lithium diborate or lithium oxalate.

[0055] (2) Add N,N'-4,4'-diphenylmethane-bismaleimide (BMI) crosslinking agent to the first mixed solution. After the crosslinking agent is completely dissolved, a viscous second mixed solution is obtained. The viscous second mixed solution is spread on a glass plate with a medical scraper to form a flat and continuous wet film. Then the cast film is vacuum dried at 90°C for 24 hours to finally obtain a self-healing electrolyte membrane for lithium-ion batteries.

[0056] 4. Preparation of self-healing lithium-ion batteries, the specific preparation process is as follows:

[0057] (1) A button cell is assembled using a lithium cobalt oxide (LCO) positive electrode and a lithium metal negative electrode. The positive electrode is prepared by hand by mixing LCO, acetylene black and PVDF in a weight ratio of 8:1:1, and the negative electrode is a lithium sheet.

[0058] (2) Dimethyl carbonate (DMC), diethylene glycol carbonate (DEC), and ethylene glycol carbonate (EC) were mixed in a volume ratio of 1:1:1 and 1M LiPF6 was added to prepare a PE film battery.

[0059] (3) The self-healing electrolyte membrane for lithium-ion batteries prepared in step 3 is sandwiched between the two electrodes, and a small amount of solution (EC:DMC = 1:1 (volume ratio), 10 μL) is added to the self-healing electrolyte membrane as a plasticizer.

[0060] Example 1

[0061] 1. Preparation of furfuryl alcohol methacrylate:

[0062] (1) Dissolve furfuryl alcohol (3.53 mL, 0.040 mol) and triethylamine (5.55 mL, 0.040 mol) in 60 mL of anhydrous tetrahydrofuran and stir at 0 °C for 2 h to obtain the first solution.

[0063] (2) Dissolve 3.87 mL of methacryloyl chloride (0.040 mol) in 40 mL of anhydrous tetrahydrofuran to obtain a second solution; then, slowly add the second solution to the first solution by titration, keeping the temperature at 0 °C during the addition. After the addition is complete, continue stirring at room temperature for 3 h to promote the reaction.

[0064] (3) After the reaction was completed, the triethylamine hydrochloride precipitate in the reaction product was separated by filtration through filter paper. The filtrate was then concentrated under vacuum to remove the solvent. Subsequently, the concentrated product was purified by silica gel rapid column chromatography using a petroleum ether / ethyl acetate (mass ratio 40:1) solvent system. The purified product F-MA was separated and collected as a pale yellow oil, with a yield of 81%.

[0065] 2. Preparation of self-healing polymer precursors:

[0066] (1) Using deionized water as solvent, a sodium dodecyl sulfate solution with a mass concentration of 2.5% was prepared under a nitrogen atmosphere and at 60°C and used as an emulsifier.

[0067] (2) Add methacrylate (MMA), butyl acrylate (BMA), and furfuryl methacrylate (F-MA) to a 2.5 wt% sodium dodecyl sulfate solution in a molar ratio of 1:2:1, and continue stirring under a nitrogen atmosphere for 2 h to form an emulsion.

[0068] (3) Using ammonium sulfate as an initiator, the initiator was added and stirred continuously for 6 hours to obtain an emulsion-like emulsion polymerization product.

[0069] (4) The emulsion polymerization product was introduced into a 3wt% Al2(SO4)3 solution to form a precipitate. The precipitate was filtered and separated, and then washed with hot deionized water (55℃) to remove residual monomers and emulsifiers and other impurities. The purified precipitate was then placed in a vacuum oven and dried at 60℃ for 12h to obtain the MMA-BMA-(F-MA) self-healing polymer precursor. The self-healing polymer precursor was placed in a desiccator for subsequent preparation of the electrolyte membrane.

[0070] 3. Preparation of self-healing electrolyte membrane:

[0071] (1) At 50°C, N-methylpyrrolidone (NMP) was used as a solution to mix MMA-BMA-(F-MA) self-healing polymer precursor and lithium diborate for 1 h to obtain a uniform first mixed solution.

[0072] (2) N,N'-4,4'-diphenylmethane-bismaleimide (BMI) crosslinking agent is added to the first mixed solution. Once the crosslinking agent is completely dissolved, a second mixed solution is obtained. The second mixed solution is mixed to a suitable viscosity and then spread onto a glass plate using a medical scraper. During the coating process, it is ensured that the solution is evenly distributed on the glass plate to form a smooth and continuous film. The cast film is then vacuum-dried at 90°C for 24 hours to form a self-healing electrolyte membrane. While ensuring complete evaporation of the solvent in the film, drying conditions should be controlled to avoid cracks or unevenness on the film surface, ensuring that the final film possesses the required physicochemical properties.

[0073] 4. Preparation of self-healing lithium-ion batteries:

[0074] (1) A button cell is assembled using lithium cobalt oxide (LCO) as the positive electrode material and lithium metal sheet as the negative electrode material. The positive electrode is prepared by mixing LCO, acetylene black and PVDF in a mass ratio of 8:1:1.

[0075] (2) A commercial liquid electrolyte containing dimethyl carbonate (DMC), diethylene glycol carbonate (DEC) and ethylene glycol carbonate (EC) in a ratio of 1:1:1 (volume ratio).

[0076] (3) Place the prepared self-healing electrolyte membrane between the positive and negative electrodes and add a small amount of solution (EC:DMC = 1:1, volume ratio, 10μL) as a plasticizer. During the assembly process, pay attention to avoid the formation of air bubbles to ensure the performance and stability of the battery.

[0077] 5. Performance Testing:

[0078] (1) Figure 3These are optical images of the self-healing polymer self-healing process in Embodiment 1 of this disclosure; by Figure 3 As can be seen, the process depicted starts from the original self-healing electrolyte membrane, then progresses to the membrane being damaged by a blade, and finally, the scratches are repaired by heating. The image shows the scratches gradually disappearing, and after a period of time, the scratches on the repaired electrolyte membrane have completely disappeared. This demonstrates that the self-healing electrolyte membrane of Example 1 can be repaired by heating after external damage.

[0079] In fact, regardless of whether the damage is caused by the formation of lithium dendrites or external damage, the self-healing electrolyte membrane of the present invention can be repaired at room temperature, and heating can accelerate the self-healing speed.

[0080] (2) Figure 4 Here is a scanning electron microscope (SEM) image of the self-healing electrolyte membrane of Embodiment 1 of this disclosure; Figure 4 The porous structure shown by electron microscopy is evidence that lithium ions can pass through the electrolyte membrane quickly, fully demonstrating that the self-healing electrolyte membrane of Example 1 can be used as an electrolyte membrane.

[0081] (3) Figure 5 The tensile strength curve of the self-healing electrolyte membrane of Embodiment 1 of the present invention; Figure 5 The two curves in the figure are the original tensile strength curve of the self-healing electrolyte membrane of Example 1 and the tensile strength curve after 24 hours of heat recovery from damage. By comparing the two curves, it can be seen that the tensile strength of the self-healing electrolyte membrane of Example 1 did not decrease significantly after self-repair, and the self-healing electrolyte membrane has good mechanical properties.

[0082] (4) The electrochemical performance was evaluated using assembled button cells. Specifically, a linear sweep voltammetry curve was used to test the self-healing electrolyte membrane to maintain a stable voltage. An AC impedance spectroscopy was used to monitor the impedance change over time to determine the compatibility between the self-healing electrolyte membrane and lithium ions. The relevant ionic conductivity (σ) was calculated from the bulk electrolyte resistance (R) according to the following equation: σ = l / (RA), where R is the resistance of the bulk electrolyte, l is the thickness of the membrane, and A is the area of ​​the electrode covered by the thin film. Figure 6 The figures show the discharge capacity of the PE membrane and the self-healing electrolyte membrane in Embodiment 1 of this disclosure at different C-rates during cycling. The figures show that the PE membrane and the self-healing electrolyte membrane of Embodiment 1 have essentially the same discharge capacity during cycling at different C-rates.

[0083] The various embodiments of this disclosure have been described above. These descriptions are exemplary and not exhaustive, and are not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical applications, or technical improvements to the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a self-healing electrolyte membrane for lithium-ion batteries, characterized in that, include: A self-healing polymer precursor was prepared by emulsion polymerization of methacrylate, butyl acrylate and furfuryl methacrylate. The self-healing electrolyte membrane is obtained by coating a mixed solution containing the self-healing polymer precursor, lithium salt and crosslinking agent onto a substrate until a dry film is formed. The method for preparing the self-healing polymer precursor includes: The methacrylate, butyl acrylate and furfuryl methacrylate are added to the emulsifier according to the set ratio, and the mixture is stirred in an inert atmosphere to form an emulsion. An initiator is added to the emulsion to carry out the emulsion polymerization. The precipitate of the emulsion polymerization product is purified and dried to obtain the self-healing polymer precursor. The method for preparing the mixed solution comprising the self-healing polymer precursor, lithium salt and crosslinking agent includes: mixing the self-healing polymer precursor and the lithium salt in a solvent at a set temperature, adding the crosslinking agent to the mixture, and completely dissolving the crosslinking agent to obtain the mixed solution; The crosslinking agent is N,N'-4,4'-diphenylmethane-bismaleimide.

2. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The set ratio is the molar ratio of methacrylate, butyl acrylate and furfuryl methacrylate of 1:2:

1.

3. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The emulsifier is sodium dodecyl sulfate with a mass concentration of 2.5%, prepared under a nitrogen atmosphere, using deionized water as a solvent, and at 60°C.

4. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The initiator is ammonium sulfate.

5. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The method for obtaining the precipitate includes: adding the emulsified polymerization product to a 3wt% Al2(SO4)3 solution to generate a precipitate, filtering and separating the precipitate to obtain the precipitate.

6. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The purification process includes washing the precipitate with deionized water at a temperature of 50°C-60°C to remove residual monomers and emulsifiers.

7. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The drying method includes drying the purified precipitate in a vacuum oven at 60°C for 12 hours.

8. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The set temperature is 50°C; The solvent is N-methylpyrrolidone; The lithium salts include lithium diborate and lithium oxalate.

9. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The method for preparing furfuryl methacrylate includes: An anhydrous tetrahydrofuran solution of methacryloyl chloride was added dropwise to an anhydrous tetrahydrofuran solution of furfuryl alcohol and triethylamine prepared at 0°C. After the addition was completed, the mixture was stirred at room temperature for a set time to obtain the reaction product. After concentrating the filtrate of the reaction product under vacuum conditions, the concentrate is purified by column chromatography to obtain furfuryl methacrylate.

10. The method for preparing a self-healing electrolyte membrane according to claim 9, characterized in that: The molar ratio of furfuryl alcohol, triethylamine, and methacrylamide chloride is 1:1:1; The stirring reaction time is set to 3 hours; The solvent used for column chromatography purification was petroleum ether / ethyl acetate at a mass ratio of 40:

1.

11. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The substrate is a glass plate.

12. The method for preparing a self-healing electrolyte membrane according to claim 1, characterized in that: The method for forming a dry film includes: drying a wet film coated on the substrate under vacuum at 90°C for 24 hours.

13. A self-healing electrolyte membrane for lithium-ion batteries, characterized in that, It is prepared by the method described in any one of claims 1-12.

Citation Information

Patent Citations

  • Self-healing polymer electrolyte membrane and its preparation method, battery

    CN113193235B

  • Polymer for lithium ion secondary battery and lithium ion secondary battery using same

    CN101156259A

  • Self-repairing polymer electrolyte matrix and preparation method thereof, self-repairing polymer electrolyte, lithium ion battery and application thereof

    CN109659605A